The Alamo [videorecording (DVD)] - Haffner, Craig; Rogers, Kenny (A & E Home Video, 2003)
"Remember the Alamo": New research dispels some long-held beliefs about what really happened in the showdown between Santa Anna's army and Davy Crockett, William Barret Travis, Jim Bowie, and their group of American volunteers. "Real west: the battle of the Alamo" : Host Kenny Rogers focuses on the strained collaboration among Davy Crockett, Jim Bowie and William Barret Travis. "Real west: the Texas rangers" : Ride into the past to see how these legendary lawmen patrolled a vast and wild territory. "Biography: Davy Crockett: American frontier legend" : Experts explode the myths surrounding the backwoodsman who died at the Alamo.